Pediatric cochlear implantation: The impact of frequency-to-place mismatch after a three-year follow-up - Nezar Hamed; Asma Alahmadi; Isra Aljazeeri; Yassin Abdelsamad; Hanaa Alotaibi; Abdulrahman Hagr; Medhat Yousef (PLoS ONE, 2025)
Introduction Frequency-to-place mismatch in cochlear implants (CIs) may influence auditory and speech outcomes, yet its impact on pediatric patients remains underexplored. This study aims to assess the impact of frequency-to-place mismatch on hearing and speech outcomes. Materials and methods In this retrospective study, the angular insertion depth and center frequency of each electrode contact were derived. The difference between the tonotopic and default frequency was used to estimate the mismatch. The impact of this mismatch on auditory and speech outcomes was assessed in pediatric CI users. Results This study included 89 implanted ears of young children. The analysis revealed a significant difference between default and postoperative electrode frequencies, with greater mismatches observed in shorter electrode arrays. A weak but significant correlation was observed between mismatch and sound field-aided thresholds (SF-AT), while no clear trends were found in other outcome measures. Patients with lower mismatches tended to perform better, while those with mismatches exceeding 7 semitones showed slightly lower—though non-significant—speech performance. However, a significant difference was observed in SIR, favoring the lower mismatch group. Conclusion Children with <7 semitones of fequency-to-place mismatch showed better, though non-significant, outcomes across multiple measures—including SDS, CAP, and SF-AT—and a significant difference in SIR. Despite no significant linear correlations overall, these findings suggest that specific mismatch levels may still influence outcomes after three years of CI use. Future studies should investigate whether tonotopic-based mapping improves speech perception and overall auditory performance in young CI users.